Grain boundary Fe-doping effects in LSGM - Gomes, Eduarda (2008)
The electrical properties of La0.95Sr0.05Ga0.90Mg0.10O3 − δ (LSGM) were modified by selective doping of the grain boundaries, using LaFeO3 screen-printed layers and annealing at high temperature to promote Fe diffusion into LSGM. Scanning electron microscopy (SEM) and energydispersive spectroscopy (EDS) analyses showed that iron was mainly located along the grain boundaries with the bulk grain composition almost unchanged. Impedance spectra showed a significant increase in the total conductivity for the Fe-doped samples, the effect being greater for the grain boundary contribution. The formation of a parallel pathway for electronic conduction along the grain boundaries explains these effects. Ageing of these samples at high temperature, after removal of the Fe source, showed a steady shift to the original LSGM behaviour, due to dilution of Fe throughout the samples.